1992
DOI: 10.1016/0014-5793(92)81436-p
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of a cardioactive neuropeptide from the tobacco hawkmoth, Manduca sexta

Abstract: The amino acid sequence of the first of a family of insect cardioregulatory peptides from the tobacco hawkmoth, Manduca sexta, has been detern~ined using a combination of Edman degradation mlerosequencmg and mass spectroscopy This peptide contmns 9 amino acid residues and an observed mass for the monoL~otop~c protonated mol~ule of 956 4 Da. There are two ¢ystemes at pnstt~ons 3 and 9 forming a disulfide bridge and the carboxyl-terminns l~ amldated. The ~tructure of this peptide, Pro-Phe-Cy~-Asn-Aia-Phe-Thr-Gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 13 publications
2
33
0
1
Order By: Relevance
“…A likely possibility is that it leads to changes in neuronal excitability, and this hypothesis is consistent with the reports of the release of CCAP at the time of ecdysis (Tublitz and Truman, 1985;Cheung et al, 1992). Such changes could be achieved by the direct gating of ionic channel by cGMP, as is known to occur in photoreceptor and olfactory neurons (Latorre et al, 199 l), or by modifying their kinetic properties by phosphorylation, which accounts, for instance, for the increase in calcium current of some snail neurons (Paupardin-Tritsch et al, 1986).…”
Section: Function Of Cgmp Responsesupporting
confidence: 89%
See 2 more Smart Citations
“…A likely possibility is that it leads to changes in neuronal excitability, and this hypothesis is consistent with the reports of the release of CCAP at the time of ecdysis (Tublitz and Truman, 1985;Cheung et al, 1992). Such changes could be achieved by the direct gating of ionic channel by cGMP, as is known to occur in photoreceptor and olfactory neurons (Latorre et al, 199 l), or by modifying their kinetic properties by phosphorylation, which accounts, for instance, for the increase in calcium current of some snail neurons (Paupardin-Tritsch et al, 1986).…”
Section: Function Of Cgmp Responsesupporting
confidence: 89%
“…Both pairs of neurons in each abdominal ganglion are peptidergic neurons that are immunoreactive for crustacean cardioactive peptide (CCAP, Fig. 3A,B), a peptide that is present in the abdominal CNS of Manduca (Cheung et al, 1992). One pair of these cells, Cell 27 (Taghert and Truman, 1982), are projection neurons that extend to the next posterior segment and terminate distally on the alary muscle of the heart and proximally in a neurohemal structure, the perivisceral organs (Davis et al, 1993).…”
Section: Identity Of Cgmp-immunoreactive Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is now an extensive literature documenting the presence of CCAP-like immunoreactivity in a large number of arthropod species (Cheung et al, 1992;Keller, 1992;Davis et al, 1993;Furuya et al, 1993;Lehman et al, 1993;Dircksen, 1994;Trube et al, 1994;Breidbach et al, 1995;Groome and Lehman, 1995;Würden and Homberg, 1995), the physiological actions of CCAP have been considerably less intensively studied. Although CCAP was initially named because of its cardioexcitatory actions on semi-isolated heart preparations of the crab C. maenas (Stangier et al, 1987), not all crustacean hearts seem to be sensitive to CCAP (McGaw et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…CCAP was first purified and sequenced from the crab Carcinus maenas (Stangier et al, 1987), and has since been found in a large number of arthropod species (Stangier et al, 1989;Cheung et al, 1992;Furuya et al, 1993;Lehman et al, 1993;Dircksen, 1994).…”
Section: Abstract: Pyloric Rhythm; Crustacean Neuropeptide; Central mentioning
confidence: 99%